AFRP Influence on Parallel Bamboo Strand Lumber Beams - Huizhong Zhang; Haitao Li; Ileana Corbi; Ottavia Corbi; Gang Wu; Chengjie Zhao; Tongwei Cao (Sensors, 2018)
The mechanical properties of parallel bamboo strand lumber beams could be improved by aramid fiber reinforced polymer (AFRP). So far, no investigation has been conducted on the strengthening of engineering bamboo beams using AFRP. In order to study the efficiency of AFRP reinforcement on parallel bamboo strand lumber beams, 13 beams had been tested and analyzed. Strain gauges and Laser Displacement Sensors were used for the tests. By sensing the strain and deformation data for the specimens under the applied loads, the results showed that AFRP can effectively improve the flexural mechanical properties of parallel bamboo strand lumber beams. However, this reinforcement cannot increase the deflection of bamboo beams indefinitely. When the cloth ratio was 0.48, the deflection of the specimens reached its maximum. With the increase of cloth ratio, the stiffness of parallel bamboo strand lumber beams was increasing. When the cloth ratio reached 0.72%, compared with the un-reinforced specimen, the stiffness increased by 15%. Therefore, it can be inferred that bonding AFRP on the considered specimens can increase the stiffness of parallel bamboo strand lumber beams. The ductility of the specimen can be effectively enhanced by adopting the AFRP provision.